Aromatase inhibitors associated with knee subchondral bone expansion without cartilage loss. (December 2013) - Davis, S. R.; Bell, R. J.; Wang, Y.; Hanna, F.; Davies-Tuck, M.; Bell, R.; Chirgwin, J.; Cicuttini, F.
Abstract Background The profound estrogen depletion caused by aromatase inhibitors (AIs) is associated with musculoskeletal symptoms, but the underlying pathophysiology remains unclear. Objective To assess the effects of AI therapy on structural changes in knee cartilage and subchondral bone over 2 years in postmenopausal women. Setting and participants Thirty women with breast cancer, mean age 58.5 (standard deviation ± 5.6) years and 62 healthy controls, mean age 56.5 (standard deviation ± 4.6) years. Main outcome measures Annualized changes in tibial cartilage volume and subchondral bone area, and worsening of tibiofemoral cartilage defects from paired knee magnetic resonance imaging 2 years apart were compared between the two groups. Results The AI-treated women had significantly greater expansion of the tibial plateau than the control group. The mean annualized differences, after adjusting for age, body mass index and baseline bone area, were 22.1 mm2 (95% confidence interval (CI) 7.6–36.6, p = 0.003) for the medial tibial plateau and 19.1 mm2 (95% CI 9.6–28.5, p < 0.001) for the lateral tibial plateau. The annual change in tibial cartilage volume and the worsening of cartilage defects did not differ between women taking AI therapy and controls. Conclusions AI therapy is associated with knee subchondral bone expansion knee with no effect on knee cartilage in postmenopausal women without pre-existing joint symptoms. This suggests the effect of severe estrogen depletion on knee is on bone, with the tibial bone expansion most likely a response to mechanical load in the setting of bone loss. Whether this then results in an increased risk of knee osteoarthritis will need to be determined.